Insulin-like growth factor binding protein-6 modulates proliferative antagonism in response to progesterone in breast cancer - Lariz, Francisco J.; Botero, Pacha B.; Shoffstall, Isabella; Houston, Kevin D. (Frontiers in Endocrinology, 2024)
Breast cancer is one of the most diagnosed cancers worldwide. The insulin-like growth factor (IGF) system promotes proliferation and survival in breast cancer cells and is regulated by 6 insulin-like growth factor binding proteins (IGFBPs). The IGFBPs sequester IGFs to prolong their half-life and attenuate binding to insulin-like growth factor 1 receptor (IGF1R). While IGFBP-6 has been studied in some cancers it has not been studied extensively in hormone receptor positive breast cancer. Survival analysis using available databases indicated that high IGFBP-6 levels improve overall survival in progesterone receptor positive breast cancers. IGFBP-6 is transcriptionally induced by progesterone in T47D breast cancer cells resulting in increased intracellular and extracellular IGFBP-6 protein. Knockdown of IGFBP-6 resulted in reduced proliferative antagonism when estradiol stimulated T47D cells were cotreated with progesterone and protein levels of both progesterone receptor isoforms (PR-A and PR-B) were decreased following knockdown of IGFBP-6. P21(Cip1/Waf1), which is progesterone responsive, was not induced in response to progesterone following knockdown of IGFBP-6. Cyclin E2, a cell cycle regulator, is induced by progesterone only when IGFBP-6 is knocked down. Stable overexpression of IGFBP-6 in MCF-7 cells resulted in an increase in Epidermal Growth Factor Receptor (EGFR) and this expression was further enhanced when cells were cotreated with progesterone and estradiol. These results indicate that IGFBP-6 is a regulator of progesterone action, and that PR is required for the observed protective effects of IGFBP-6 in breast cancer.